2012
DOI: 10.1155/2012/298732
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Putative Biomarkers: The Role of Alpha 2 and 6 Integrins in Susceptibility, Treatment, and Prognosis

Abstract: The genetic architecture underpinning prostate cancer is complex, polygenic and despite recent significant advances many questions remain. Advances in genetic technologies have greatly improved our ability to identify genetic variants associated with complex disease including prostate cancer. Genome-wide association studies (GWASs) and microarray gene expression studies have identified genetic associations with prostate cancer susceptibility and tumour development. The integrins feature prominently in both stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
4
11
0
Order By: Relevance
“…Consistent with our results, ITGA6 overexpression was observed in esophageal cancer [48] and colon cancer, [49] and it not only mediates interaction with the ECM but also drives intracellular signaling events that communicate from the tumor microenvironment to inside of the tumor cell to alter phenotypes including migration and invasion. [50] The associations of the ITGA6 with prognosis in cancer is poorly known, with limited studies reporting that this gene affects the prognosis of prostate cancer by influencing the biological characteristics of CSC, [51] and its high expression exhibited significantly poorer OS, [52] which is consistent with our finding in ovarian cancer (Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, ITGA6 overexpression was observed in esophageal cancer [48] and colon cancer, [49] and it not only mediates interaction with the ECM but also drives intracellular signaling events that communicate from the tumor microenvironment to inside of the tumor cell to alter phenotypes including migration and invasion. [50] The associations of the ITGA6 with prognosis in cancer is poorly known, with limited studies reporting that this gene affects the prognosis of prostate cancer by influencing the biological characteristics of CSC, [51] and its high expression exhibited significantly poorer OS, [52] which is consistent with our finding in ovarian cancer (Fig. 5).…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, integrin upregulation in PCa has been linked to lymph node metastases and aggressive disease. It is proposed that a subpopulation of PCa cells harboring integrin upregulation exhibit cancer stem cell like characteristics conferring metastatic potential (7). Hence, BAF57 mediated control of α2 integrin signaling has important ramifications for therapeutic response and resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling has determined that diverse mechanisms of inappropriate AR reactivation and function, such as AR amplification, splicing, post-translational modifications, chromosomal translocations, AR interplay with a variety of co-modulators such as chemokines (e.g., CXCL12), oncogenes (e.g., c-myc and c-src) and coactivators (e.g., CBP, SRC family) fuel the development of aggressive CRPC and subsequent metastasis (reviewed in (6)). Advanced PCa is lethal and successful disease management depends on identifying reliable biomarkers that signal the propensity to metastasize and utilizing potential new candidates for therapeutic targeting (7). …”
Section: Introductionmentioning
confidence: 99%
“…Many metastatic genes and metastatic suppressor genes have been identified, suggesting that there are many alternative metastasis pathways [7]. Furthermore, the genome of metastatic tumor cells has greater instability than nonmetastatic tumor cells; thus metastatic tumor cells acquire multiple intrinsic genetic and epigenetic changes that are attributable to their metastatic phenotype [8], including genes encoding cell adhesion molecules (CAMs), such as E-cadherin [9], CD44 [10], integrin αVβ3 [11], integrins α2 & α6 [12], and METCAM/MUC18 [13][14][15]. Since cell-adhesion molecules govern the social behaviors of cells, the altered expressions of CAM genes are doomed to affect the motility and invasiveness of many tumor cells in vitro and their metastasis in vivo [16,17].…”
Section: Introduction: Biomarkers Of Prostate Cancermentioning
confidence: 99%
“…Furthermore, altered expressions of cell adhesion molecules (CAMs) in metastatic cells may increase their ability to interact with the extra-cellular matrix and establish secondary growth in a favorable soil (a favorable growth microenvironment or niche in the distant organs that had been conditioned by the tumor cells in the micrometastases) [19]. Studies of the altered expression of CAMs in prostate cancers have been limited to E-cadherin [9], CD44 [10], some integrins [11,12], and CEA-CAM 1 [21]. From our studies on the effect of the expression of cell adhesion molecules on the prostate cancer metastasis, we have found that huMETCAM/MUC18 is a bona fide metastatic gene and it very likely plays a role in converting an indolent prostate cancer to an aggressive one [13][14][15][22][23][24][25][26][27]].…”
Section: Introduction: Biomarkers Of Prostate Cancermentioning
confidence: 99%